Pro Bono Awards Reception at State Bar Annual Meeting in Monterey - Watkins, Howard::::::::: (1984)
Eight Pro Bono Award recipients holding their framed certificates: Kenneth Prag, Virginia Talmage, wife of Dale Minami, Simone Campbell, Thomas Daly, Jr., Amelia Albano, Ronald Vincent LoLordo, Rodrigo Mayorga,